Chapter Characterization of Atmospheric Mercury in the High-Altitude Background Station and Coastal Urban City in South Asia - Bharath, Karuppasamy (InTechOpen, 2020)
This study is performed to evaluate the potential sources and seasonal variation of atmospheric mercury (Hg) emissions from regional sources and other influences in India. To achieve this, using the gold amalgam technique with an automated continuous mercury vapour analyzer (TekranTM 2537B). To assess the total gaseous mercury in high altitude mountain peak station at Kodaikanal & coastal/urban air in Chennai region, the impact of changing weather conditions is also evaluated. To compare the past and recent reports of mercury at different locations in the world. The average total gaseous mercury value in Chennai is 4.68 ng/m3, which is higher as compared to Kodaikanal, where it is 1.53 ng/m3. The association between TGM with meteorological parameters in ambient air such as temperature, relative humidity, rainfall intensity, the direction of wind and velocity of was studied. The TGM concentration in India are compared with other nations, the TGM levels are similar to the east and Southeast Asian countries, and also Europe, Sub-Saharan Africa and North America are the averages and maximum concentration generally smaller. This research will help to establish more effective management approaches to mitigate the impacts of atmospheric mercury on the rural and urban environment.